Effect of the preparation conditions on the properties of Fe-Pt nanoparticles produced by sonoelectrodeposition - Luong, Nguyen Hoang; Hai, Nguyen Hoang; Phu, Nguyen Dang (VNU Journal of Science: Mathematics - Physics; Vol 25 No 1, 2009)
Abstract